The Adoption of Holacracy in Higher Education: A Scale Development Study - Merve Turpçu (Üniversite Araştırmaları Dergisi)
This study aims to develop a valid, reliable, and convenient data collection tool to measure the level of faculty members’ adoption of the holacracy model in university administration. The data of this study were obtained from faculty members working in the faculties of education of state universities in Türkiye in the 2020-2021 academic year. Participation in the study was completely voluntary. The data were collected from a sample of 268 people. Within the scope of the research, the Higher Education Holacracy Scale (HEHS) was used as a data collection tool. The researcher developed the draft form of the HEHS in line with the literature on holacracy. The draft form was presented to 14 experts, one of whom was an expert in measurement and evaluation. Thus, the content validity of the research was ensured. As a result of the analyses, it was determined that the variance explained was 63.228%, the structure consisted of three components, and the fit index values were at a good level. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted for the validity of the scale, and Cronbach’s Alpha coefficient was calculated for reliability. Item-total correlations examined the discrimination of the scale items. After the analyses, it was determined that this 25-item scale, which is in harmony with its theoretical foundations, is a valid and reliable scale suitable for measuring faculty members’ opinions.